A thematic analysis of influences on parents' autism intervention decisions. (October 2021) - Wilson, Meghan; Whelan, Thomas; Milne, Lisa; Hamilton, David; Jacobs, Diane; Pilkington, Pamela
Highlights: A thematic analysis was used to identify influences on parents' autism intervention decisions. Parents discussed how they found and selected interventions. Individual needs of children and families were prioritised in decision-making. Aspects related to intervention acceptability and access issues (e.g., funding and availability) influenced decisions. Understanding parents' perspectives is important for collaborative decision-making. Abstract: Background: Factors impacting parents' selection of interventions for their child on the autism spectrum need to be understood in order to better support decision-making. The aim of the current study was to explore parent-reported influences on decisions. Method: A sample of 14 Australian parents (13 mothers; 1 father) of a child (4–11 years) diagnosed on the autism spectrum were interviewed about their decisions regarding the use of interventions. A thematic analysis was used to identify prominent themes. Findings: A total of three themes, comprising 11 subthemes were identified. The primary themes were: finding interventions; meeting child and family needs; and acceptability and access. Conclusion: Parents' responses highlighted influences on decisions to use evidence-based practices (e.g., behavioural therapies and social skills programs), as well as those with limited empirical support (e.g., animal-assisted therapy and dietary intervention). Influences frequently reported in extant research were reported by parents in this study (e.g., recommendations, logistics of access, and children's individual needs) as well as issues that warrant further investigation (e.g., coping with challenges and stress, importance of intervention intensity, and consideration of the whole family).